ON POSSIBLE ATTRIBUTION OF CHAIN-ARMOR ITEMS FROM THE MILITARY BURIALS OF SADONSKOY BURIAL GROUND - Kadzaeva, Zalina Petrovna; Malasev, Vladimir Ur'evic (History, Archeology and Ethnography of the Caucasus, 2020)
Small fragments of chain-mail armor and chain-mail sections were obtained from the military burials of the early Middle Ages. Researchers consider these items as part of underclothes chain-armor, placed in the burial as a symbol. Due to the small size, they are often interpreted as chain breastplates or pectorals. The authors suggest a new ascription of the said items. The paper analyzes the findings of chainmail pieces from two military burials of the early medieval Sadonsky cemetery of Alan culture. By analogy with similar artifacts from chronologically close military burials of the Lombards of the Castel Trozino burial ground in Italy, the pieces from Sadon are supposedly interpreted as gloves designed to protect the hand in combat. Fragments of leather preserved on chain mail items from Sadon may be the remains of items in the form of gauntlets or gloves; from the back side a rectangular piece of chain mail was sewn to them to protect the hand. Since these objects were found in the burials in single copy, as well as in the burials of Castel Trozino, it can be assumed that protective gloves were intended only for one hand, as the other hand was protected by a shield. The study also presents other findings of chain mail items from military burials, mainly from the burial grounds in the North Caucasus, which, in our opinion, are similar to the Sadon and Lombard pieces.The archaeological, ethnographic and iconographic information on the methods of protecting the hand, given in the study, indicates that gloves as an element of protective military equipment were known from the Early Middle Ages to the New Age. Based on the information above, as a hypothesis, we can assume that gloves with a chainmail mesh sewn on could exist in the Early Middle Ages among the population of the North Caucasus. In this case, the published material from Sadon refer to elements of protective equipment and allow us to consider the existence in the 7th century in the Alans of the North Caucasus of chain-mail gloves designed to protect the wrist of one of the hands in battle.
Keywords: early Middle-Ages; Alan culture; Sadonsky burial ground; chainmail items; protective equipment; gloves.